Techno-economic environmental risk analysis of sustainable power systems. - Pagone, Emanuele (Cranfield University, 2018)
Sustainable engine systems are undoubtedly one of the main topics at the centre of the recent scientific debate. A significant number of novel thermodynamic concepts, partly based on gas turbine engines, are available in the open scientific literature and have been scarcely investigated. Cranfield University has developed an integrated, modular, multi-disciplinary framework of computational software called Techno-economic Environmental Risk Analysis (TERA) to assess complex, thermodynamic cycles from an integrated point of view. The present study completes a TERA work on sustainable power systems in two steps. Initially, the entire TERA methodology is applied to the aviation field with the integration of a set of modules to investigate three novel, turbofan, aircraft engines. Namely, the mentioned concepts are featured by: a counter-rotating core for short range (GTCRSR), an active core for short range (GTACSR), and an inter-cooler for Long Range (GTICLR). The optimised design specifications of the GTCRSR engine show a reduction of more than 7% of block fuel in comparison to the reference engine, more than 6% for the GTACSR and almost up to 5% for the GTICLR. Subsequently, a library of electric power generation future technology concepts has been built to be merged in the TERA for energy framework, developing the relevant computational codes. The power plants chosen encompass different domains of the field and are: the Advanced Zero Emissions Power plant — AZEP (carbon capture and storage concept); a supercritical steam turbine power plant (for nuclear applications); a land-based wind farm working in synergy with a conventional power plant. Multiple, specific control strategies for the fossil fuel and nuclear power plant have been identified to handle the power output down to 60% of the design point for the AZEP and slightly below 80% for the nuclear cycle. Hourly performance simulations of typical days representative of each season of the wind farm in combination to conventional gas turbine engines have been investigated for different size (from 223 MW to 5 MW at full load).
Keywords: Techno-economic environmental risk analysis (TERA); sustainable power systems; novel; turbofan; aircraft engines; counter-rotating core; active core; inter-cooler core